Ritual of Worshipping the God of Wealth "Kongco Han Tan Kong" at Bio Dewa Rejeki Sentul, Bogor: An Anthropolinguistic Study (International Journal of Education and Literature, 2025)
This study investigates the ritual of worshipping the God of Fortune, particularly Kongco Han Tan Kong, as practiced by the Chinese-Indonesian community in Sentul, Bogor, where Bio Dewa Rejeki serves as the central site of ritual performance. Viewed through an anthropolinguistic lens, the research explores the interplay between language and cultural practices within the ritual, employing an ethnographic approach to examine the meanings, symbols, and values embedded in it, as well as their role in shaping communal identity. Beyond its religious dimension, the ritual reflects complex social and cultural dynamics, functioning as a mechanism for reinforcing solidarity and fostering identity amidst rapid social change. Statistical data indicate a significant rise in visitors to Bio Dewa Rejeki during the Lunar New Year celebration, averaging 5,000 daily visitors, thereby highlighting its strong appeal and integrative role within the local community while also attracting interest from non-Chinese participants seeking spiritual experience. Data collection is conducted through participant observation and in-depth interviews with organizers and participants over several months, providing a comprehensive understanding of the ritual’s implementation, symbolic meanings, and perceived significance in daily life. The findings are expected to contribute to a broader understanding of the interrelationship between language, culture, and religious practice within the Chinese-Indonesian community, underscoring the central role of language and communication in shaping spiritual experience and communal identity.